Kinematic, dynamic and stress analysis of an assistive robotic arm - Wang, Chao (Nanyang Technological University, 2022)
This report presents the design, analysis, and improvements of an assistive robotic arm intended for wheelchair-bound stroke patients to enable them to finish some daily activities at home. In this report, a 2RRR-P-S configuration of the robotic arm is described. This configuration consists of the spherical base mechanism, telescopic rod, cable mechanism, and the end-effector. This will allow for 6 Degrees of Freedom (DOFs), enabling the patient to cover a wide workspace while having minimal load on the motors. Then a new design of the end-effector is carried out with the attachment to the selected load cell. After going through the design and the advantages it brings, the stress analysis of the spherical base mechanism is conducted to get the stresses of different telescopic rod lengths and different positions and to find the maximum value. In order to ensure the safety of the links, the cross-sectional size is increased. In the last chapter, a new configuration is proposed. A rotation joint is added under the cable mechanism. There are 7 DOFs in total which allows a more flexible movement. Instead of connecting the cable mechanism to the middle of the end-effector, the new design connects the cable mechanism to one end of the end-effector. This design makes the control point closer to the wrist and gives more wrist-based assistance.